Inducing ferroptosis has the potential to overcome therapy resistance in breast cancer - Qi, Xiaowen; Wan, Zhixing; Jiang, Baohong; Ouyang, Yuhan; Feng, Wenjie; Zhu, Hongbo; Tan, Yeru; He, Rongfang; Xie, Liming; Li, Yuehua (Frontiers in Immunology, 2022)
Breast cancer is the most common type of malignancy among women. Due to the iron-dependent character of breast cancer cells, they are more sensitive to ferroptosis compared to normal cells. Induction of ferroptosis in breast cancer cells inhibits cell proliferation, resolves tumor drug resistance, and improves tumor treatment outcome. Ferroptosis is highly dependent on the balance of oxidative and antioxidant status. When ferroptosis occurs, intracellular iron levels are significantly increased, leading to increased membrane lipid peroxidation and ultimately triggering ferroptosis. Ferroptotic death is a form of autophagy-associated cell death. Synergistic use of nanoparticle-loaded ferroptosis-inducer with radiotherapy and chemotherapy achieves more significant tumor suppression and inhibits the growth of breast cancer by targeting cancer tissues, enhancing the sensitivity of cells to drugs, reducing the drug resistance of cancer cells and the toxicity of drugs. In this review, we present the current status of breast cancer and the mechanisms of ferroptosis. It is hopeful for us to realize effective treatment of breast cancer through targeted ferroptosis.